Strengthening Local Government Offices with Data-Based Work Planning and Performance Improvement - al Qordhowi, Andrian Firdaus Yusuf (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This community service article examines the persistent gap between normative expectations of data-driven work planning and the limited performance improvements observed in local government offices. Although data-based governance is widely promoted, planning practices often remain compliance-oriented and weakly linked to measurable outcomes. The program aims to strengthen local government capacity to implement data-driven planning as a strategic mechanism for performance improvement. Using a Participatory Action Research (PAR) approach, government staff were actively involved in cycles of problem diagnosis, planning redesign, action, reflection, and evaluation. Data were collected through document analysis, surveys, participatory observation, and institutional performance records, and analyzed using mixed qualitative analysis and correlation tests. The findings show a substantial shift toward evidence-based planning, improved alignment between data, targets, and performance indicators, and a positive correlation between the intensity of data-driven planning and performance achievement. The study demonstrates that participatory engagement transforms data use from procedural compliance into analytical decision-making and offers a replicable model for institutional strengthening in local governance.